3D Modeling of craniofacial ontogeny and sexual dimorphism in children. Issue 9 (26th December 2020) - Smith, Olivia A. M.; Nashed, Youssef S. G.; Duncan, Christian; Pears, Nick; Profico, Antonio; O'Higgins, Paul
Abstract: Background: The range of normal variation of growth and development of the craniofacial region is of direct clinical interest but incompletely understood. Here we develop a statistical model of craniofacial growth and development to compare craniofacial ontogeny between age groups and sexes and pilot an approach to modeling that is relatively straightforward to apply in the context of clinical research and assessment. Methods: The sample comprises head surface meshes captured using a 3dMD five‐camera system from 65 males and 47 females (range 3–20 years) from the Headspace project, Liverpool, UK. The surface meshes were parameterized using 16 anatomical landmarks and 59 semilandmarks on curves and surfaces. Modes and degrees of growth and development were assessed and compared among ages and sexes using Procrustes based geometric morphometric methods. Results: Regression analyses indicate that 3–10 year olds undergo greater changes than 11–20 year olds and that craniofacial growth and development differs between these age groups. The analyses indicate that males extend growth allometrically into larger size ranges, contributing substantially to adult dimorphism. Comparisons of ontogenetic trajectories between sexes find no significant differences, yet when hypermorphosis is accounted for in the older age group there is a significant residual sexual dimorphism. Conclusions: The study adds to knowledge of how adult craniofacial form and sexual dimorphism develop. It was carried out using readily available software which facilitates replication of this work in diverse populations to underpin clinical assessment of deformity and the outcomes of corrective interventions.